MPGN II - genetically determined by defective complement regulation? - Licht, Christoph; Schlötzer-Schrehardt, Ursula; Kirschfink, Michael; Zipfel, Peter F.; Hoppe, Bernd (Pediatric nephrology, 2007)
MPGN II is a rare disease which is characterized by complement containing deposits within the GBM. The disease is characterized by functional impairment of the GBM causing progressive loss of renal function eventually resulting in end stage renal disease.
published online: 23 September 2006
Gesehen am 15.02.2021